Exploring Preservice English Students’ Experiences in Using English Songs for Vocabulary Learning - Intan Yunita (Cipta Pustaka Nusantara, 2026)
This study explores fifth-semester preservice English students’ experiences in using English songs as a resource for vocabulary learning. Although previous studies have highlighted the benefits of songs, limited research has examined how learners use them independently in daily life. This qualitative descriptive case study involved ten fifth-semester students from the English Language Education Department at UIN Walisongo Semarang in 2025 who regularly engaged with English songs as part of their informal learning. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal three main themes: (1) vocabulary learning strategies, such as repeated listening, lyric checking, translation use, contextual guessing, and limited note-taking; (2) perceived benefits, including stronger motivation, improved retention through melody, better pronunciation, enhanced listening skills, and exposure to colloquial expressions; and (3) challenges, such as fast-paced lyrics, figurative language, slang, reduced focus, and non-standard grammar. Overall, English songs function as an enjoyable supplementary tool that supports vocabulary development, although additional strategies may be needed to maximize their effectiveness.